Investigation the Structural Influences of Silver Oxide Addition in the Bioactive Phosphate Glasses - Ruqaya H. Hussian; Dunia K. Mahdi (East European Journal of Physics, 2023)
This research investigates the impact of varying concentrations of silver oxide on the structure and morphology of phosphate bioactive glass (PBG). PBGs are gaining popularity as a potential replacement for traditional silicate glasses in biomedical applications due to their adjustable chemical resistance and exceptional bioactivity. Upon examination of the scanning electron microscope of the composites without Ag2O, it was observed that the grains tended to merge together, and the surface particles appeared to be larger than those in composites with Ag2O at concentrations of 0.25, 0.5, and 0.75 wt%. The study found that the diffraction pattern of phosphate bioactive glass composites sintered without Ag2O showed the presence of Strontium di-phosphate and Calcium di-phosphate. The XRD pattern of these composites without Ag2O revealed specific planes that corresponded to both types of di-phosphate. However, when Ag2O was added, a new cubic phase was detected, and the intensity of the calcium and strontium diphosphate increased with higher Ag2O content. The XRD pattern of the composites with Ag2O displayed specific planes that corresponded to Ag2O. In other words, the absence of Ag2O in the composite material led to larger particle sizes and less distinct boundaries between grains. In addition, it has been found that, as the concentration of Ag2O increased from 0 to 0.25, 0.5, and 0.75 wt%, the average crystallite size decreased from 36.2 to 31.7, 31.0, and 32.8 nm, respectively. These results suggest that the addition of Ag2O can effectively reduce the average crystallite size of the composite materials. Also, as the concentration of Ag2O increased from 0 g to 0.5 wt% within the composite material, the average lattice strain increased from 3.41·10-3 to 4.40·10-3. In simpler terms, adding Ag2O to the composite material resulted in a slight increase in the average lattice strain.